Análise imunoistoquímica e histomorfométrica do reparo de enxertos para teto de cavidade em levantamento de seios maxilares com a utilização de membranas de lenta e rápida degradação - Bresaola, Marco Dapievi (2015)
Oral rehabilitation of patients with vertical and horizontal jaw bone deficiency is one of the main challenges of today's dentistry. In order to improve the quality of newly formed bone within the maxillary sinus, slow and fast decay membranes began to be employed in the anterior wall of the maxillary sinus and juxtaposed Schneider membrane, as ROG technique and maintaining the particles of the graft after perforation of the membrane, respectively. Thus, the objective of this study was to evaluate the bone repair process of two bone substitutes at the interface with sinual membrane of maxillary sinuses of rabbit after sinus-lift procedures with the use of slow and fast degradation membranes. Twenty-four adult male rabbits underwent bilateral maxillary sinus lift procedures and were divided into 4 groups according to the type of graft material and membrane used: Group 1: Bio-Oss and membrane was not used; Group 2: Bio-Oss and Collagen and membrane was not used; Group 3: Bio-Oss and fast decay membrane; and Group 4: Bio-Oss and slow decay membrane. All groups were sacrificed at 30 and 120 days for microscopic analysis, histomorphometric and immunohistochemistry. Microscopy showed similar characteristics among the 4 groups, and between 30 and 120 days. Histomorphometric analysis revealed similarity of quantity, to the extent that there was no significant difference between the groups in those periods, and immunohistochemistry showed similar quality, as observed in all groups period showed intense staining for RUNX-2 and VEGF. Thus, it s possible to assume that the Bio-Oss Collagen is a great possibility,with similar results and technical facility compared to Bio-Oss for grafting in maxillary sinus, and the decision about the use of absorbable membraes in the ceiling cavity in maxillary sinus lift procedures should be guided by the outcome of Schneider's membrane detachment process, since the application of a biological membrane does not prejudice nor has guided bone regeneration character at new bone formation.